HUBUNGAN PENGETAHUAN TENTANG K3 DAN SIKAP BELAJAR DENGAN HASIL BELAJAR CHASIS SEPEDA MOTOR - Muhamad Thohir; Nurcholish Arifin Handoyono (JURNAL VOKASI DEWANTARA (JVD), 2020)
The purpose of this study was to determine: (1) the relationship between Occupational Safety and Health (K3) knowledge and learning outcomes of motorcycle chassis; (2) the relationship between learning attitudes and motorcycle chassis learning outcomes; and (3) to determine the relationship between OSH knowledge and learning attitudes with learning outcomes of motorcycle chassis. The research method uses the correlational method with a population of all class X students majoring in Motorcycle Business Engineering (TBSM) with a total of 74 students. The technique for determining samples using census techniques, ie the sample used for research is 100% of the total number of students. Data collection techniques using questionnaires, observation and documentation. The method used is descriptive quantitative with correlation analysis including hypothesis testing and prerequisite tests, prerequisite tests include normality tests, linearity tests and intercorrelation tests. The results showed that: (1) there was a significant positive relationship between K3 knowledge and learning outcomes of motorcycle chassis; (2) there is a significant positive relationship between learning attitudes and motorcycle chassis learning outcomes; and (3) there is a significant positive relationship between OSH knowledge and learning attitudes with motorcycle chassis learning outcomes.